Malayaite With Cobalt Prepared Using Mechanical Activation - Luxová, Jana; Šinkovská, Marcela; Šulcová, Petra (Česká společnost průmyslové chemie, 2016)
In this work sphene pigments of malayaite type doped by cobalt were prepared and the mechanical activation was used as a pre-treatment of the starting materials. CaCO3, SnO2, SiO2 and mixed Co3O4 were used for preparation of malayaite corresponding chemical composition CaSn(Co)SiO5-δ, with the stoichiometric ratio of Co/Sn = 0; 0.015; 0.058 and 0.093. Planetary mill Pulverisette 5 (Fritsch, Germany) was used for mechanical activation. The mechanical treated mixtures were calcinated at various temperatures (1150-1400 °C/4 hours with step 50°C) with aim to assess the effect of mechanical activation as first stage of pigment preparation with respect to their colour and optical properties. The colour properties, the particle size and the phase composition of the malayaite pigments have been investigated. Products of calcination were subjected to milling to the required particle size in order to improve optical and application properties.
Malayaity s kobaltem připravené pomocí mechanické aktivace
Keywords: Mechanical Activation; Malayaite; Colour Properties; Particle Size Distribution; Phase Analysis; Mechanická aktivace; Malayait; barevné vlastnosti; Distribuce velikosti částic; fázová analýza